Immune responses to Tilapia lake virus infection: what we know and what we don’t know - Kembou-Ringert, Japhette E.; Steinhagen, Dieter; Thompson, Kim D.; Daly, Janet M.; Adamek, Mikolaj (Frontiers in Immunology, 2023)
Tilapia Lake virus (TiLV) is a novel contagious pathogen associated with a lethal disease affecting and decimating tilapia populations on several continents across the globe. Fish viral diseases, such as Tilapia Lake virus disease (TiLVD), represent a serious threat to tilapia aquaculture. Therefore, a better understanding of the innate immune responses involved in establishing an antiviral state can help shed light on TiLV disease pathogenesis. Moreover, understanding the adaptive immune mechanisms involved in mounting protection against TiLV could greatly assist in the development of vaccination strategies aimed at controlling TiLVD. This review summarizes the current state of knowledge on the immune responses following TiLV infection. After describing the main pathological findings associated with TiLVD, both the innate and adaptive immune responses and mechanisms to TiLV infection are discussed, in both disease infection models and in vitro studies. In addition, our work, highlights research questions, knowledge gaps and research areas in the immunology of TiLV infection where further studies are needed to better understand how disease protection against TiLV is established.